Longitudinal Analysis of CCR5 and CXCR4 Usage in a Cohort of Antiretroviral Therapy-Naïve Subjects with Progressive HIV-1 Subtype C Infection - Jakobsen, M.; Cashin, K.; Roche, M.; Sterjovski, J.; Ellett, A.; Borm, K.; Flynn, J.; Erikstrup, C.; Gouillou, M.; Gray, L.; Saksena, N.; Wang, B.; et al. (2013)
HIV-1 subtype C (C-HIV) is responsible for most HIV-1 cases worldwide. Although the pathogenesis of C-HIV is thought to predominantly involve CCR5-restricted (R5) strains, we do not have a firm understanding of how frequently CXCR4-using (X4 and R5X4) variants emerge in subjects with progressive C-HIV infection. Nor do we completely understand the molecular determinants of coreceptor switching by C-HIV variants. Here, we characterized a panel of HIV-1 envelope glycoproteins (Envs) (n = 300) cloned sequentially from plasma of 21 antiretroviral therapy (ART)-naïve subjects who experienced progression from chronic to advanced stages of C-HIV infection, and show that CXCR4-using C-HIV variants emerged in only one individual. Mutagenesis studies and structural models suggest that the evolution of R5 to X4 variants in this subject principally involved acquisition of an "Ile-Gly" insertion in the gp120 V3 loop and replacement of the V3 "Gly-Pro-Gly" crown with a "Gly-Arg-Gly" motif, but that the accumulation of additional gp120 "scaffold" mutations was required for these V3 loop changes to confer functional effects. In this context, either of the V3 loop changes could confer possible transitional R5X4 phenotypes, but when present together they completely abolished CCR5 usage and conferred the X4 phenotype. Our results show that the emergence of CXCR4-using strains is rare in this cohort of untreated individuals with advanced C-HIV infection. In the subject where X4 variants did emerge, alterations in the gp120 V3 loop were necessary but not sufficient to confer CXCR4 usage. © 2013 Jakobsen et al.